Education, innovation, entrepreneurship, growth and development in Latin America (2022)
The importance of education to promote the processes inherent to innovation and entrepreneurship is currently of vital importance in professional training, which in turn links the impact it has on macroeconomic variables such as economic growth and development of an economy. In this sense, the general objective of the research is to explain the influence of education on variables such as innovation, entrepreneurship and its impact on growth and development, in this particular, in Latin American countries. From the methodological point of view, a documentary review is made regarding future projections within the framework of these variables, and a statistical analysis of cases such as America, Europe and Asia, in order to integrate the different experiences and models, taking as reference the results that in praxis are currently consonant with each one in particular. Finally, the importance of framing in education the congruence and pragmatic coherence of the objectives of public policies in terms of innovation, research, science and technology is concluded, which in turn promotes the multiplier effect in synergy with the private business sector, promoting between both variables such as growth, poverty and development.